Pengaruh Return on Asset, Net Profit Margin, Firm Size dan Debt To Equity Ratio Terhadap Harga Saham pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2015-2022 - Karlina, Ai; Hamdani, Deni (Economic Reviews Journal, 2024)
Finding and elucidating the relationship between stock prices and return on asset, net profit margin, firm size, and debt to equity ratio is the goal of this study. Secondary data from www.idx.co.id are the ones utilized. Twenty-five pharmaceutical sub-sector businesses listed on the Indonesia Stock Exchange for the Financial Report Period of 2016–2022 comprise the study population, and the sample size comprises forty financial reports from these companies. Using a purposive sampling strategy, the Sampling Technique employs nonprobability sampling. Utilizing both a descriptive and verification technique, the study methodology is quantitative. Maximum Value, Minimum Value, Mean, and Standard Deviation are the components of descriptive statistical analysis. Validation The tests used in statistical analysis include the determination coefficient test, the product moment correlation coefficient test, the multiple linear regression test, and the classical assumption test. Partially (t-test) and fully (f-test) concurrent hypothesis testing is done. The following conclusions were drawn from the partial hypothesis testing (t-test) results: (1) Return on Asset has a positive and substantial effect on stock price; (2) Net Profit Margin has no effect on stock price; and (3) Firm Size has no effect on stock price”. (4) The debt to equity ratio is unaffected by the price of stocks. Return on Asset, Net Profit Margin, Firm Size, and Debt to Equity Ratio were found to have no simultaneous effects on Stock Price based on the findings of the simultaneous hypothesis testing (f-test).